COMMUNITY ECONOMIC ZONE: AN ALTERNATIVE TO INCREASE PUBLIC WELFARE IN RURAL AREA - Muria Herlina (Lembaga Penelitian Universitas Pasundan, 2016)
Humans’ ability in fullfiling primary needs or doing their social role have an obstacle called proverty, so community cannot perform their social functions. This condition occurs in developing countries including Indonesia. Since 2014 FlipMas Indonesia (Forum Layanan Ipteks bagi masyarakat Indonesia) and CSR/BKBL PT. Pertamina (Persero) have cooperated to create an idea to decrease proverty through Social Economic Zone or also known as Kawasan Ekonomi Masyarakat (KEM) PertaminaFlip. KEM program conducts nationally by region FlipMas in many provinces and aims to increase human development index (IPM) which is a target activity focused to economic, health and education enhancement. The method used aliterature study is supported with many practices in field work nationally to know the active target community social function in KEM membership with standard success level using IPM standard Indonesia. This year is a KEM program implementation, and the reports from each province reveal that the majority of KEM activities contibuted in increasing IPM rural community especially in revenue enhancement field. The result indicates that KEM program can increase community social welfare in rural area.